Política e Ritual: a faina missionária beneditina entre os Makuxi no vale do Rio Branco - Santilli, Paulo José Brando [UNESP] (My University, 2014)
This paper deals with a reconstruction of the Benedictine missionary work in the Rio Branco valley (1909-1947), referenced to the relations established between the monks from the Monastery of São Bento do Rio de Janeiro and Macushi, people of Carib linguistic affiliation in the Guiana region. Such reconstitution reveals the tone of relations between the Indians and missionaries on the ritual production, seeking to interpret its possible meanings.

Este artigo trata de uma reconstituição da atuação missionária beneditina no Vale do Rio Branco (1909-1947), referenciada às relações estabelecidas entre os monges provenientes do Mosteiro de São Bento do Rio de Janeiro e os Makuxi, povo de filiação linguística Carib na região das Guianas. Tal reconstituição evidencia a tônica das relações estabelecidas entre os índios e os religiosos na produção ritual, buscando interpretar suas possíveis significações.
Ritual and politics: the Benedictine missionary toil among the Macushi in Rio Branco valley
Keywords: Macushi; Benedictine mission; Evangelization; Rio Branco valley; Makuxi; Beneditinos; Missão; Catequese; Vale do Rio Branco